Quantitative characterization of anisotropic properties of the interfacial transition zone (ITZ) between microfiber and cement paste - He, Shan (2019)
A new approach to characterize ITZ between microfiber and cement matrix is reported. Results show that microstructure of hydrated cement paste is highly modified in the vicinity of microfibers, with higher porosity and less anhydrous cement. ITZ can extend up to 100 μm from the interface into the matrix. The larger extent of ITZ suggests that perturbation due to inclusion of microfibers to packing of cement grains is severer than that due to inclusion of aggregates. Furthermore, ITZ between microfiber and cement matrix is highly heterogeneous along its axial direction. Existing ITZ analysis methods performed on 2-D cross-sectional plane intersecting with fiber axis thus can lead to errors and uncertainties. Mechanical properties of ITZ between microfiber and cement matrix are anisotropic. Stiffness and ductility of ITZ in the radial direction are 31% and 28% higher than that in the tangential direction, respectively.